Reconstitution of TCA cycle with DAOCS to engineer Escherichia coli into an efficient whole cell catalyst of penicillin G - Lin, Baixue; Fan, Keqiang; Zhao, Jian; Ji, Junjie; Wu, Linjun; Yang, Keqian; Tao, Yong (Proceedings of the National Academy of Sciences - PNAS, 2015)
We developed Escherichia coli expressing deacetoxycephalosporin C synthase (DAOCS) as a whole-cell biocatalyst to convert penicillin G to G-7-aminodeacetoxycephalosporanic acid (G-7-ADCA). The major strategy used was to reconstitute the tricarboxylic acid (TCA) cycle of E. coli with DAOCS catalyzed reaction; thus the metabolic flux of central metabolism was forced to go through DAOCS catalyzed reaction to produce G-7-ADCA. This strategy was combined with engineering efforts to reduce the accumulation of acetate and the degradation of penicillin G and G-7-ADCA to improve the conversion rate of penicillin G by DAOCS significantly. Therefore, this work demonstrates the feasibility to redirect the TCA cycle to drive a desired enzyme reaction, and this strategy could be applied to other enzymes that catalyze TCA cycle-coupleable reactions. Many medically useful semisynthetic cephalosporins are derived from 7-aminodeacetoxycephalosporanic acid (7-ADCA), which has been traditionally made by the polluting chemical method. Here, a whole-cell biocatalytic process based on an engineered Escherichia coli strain expressing 2-oxoglutarate–dependent deacetoxycephalosporin C synthase (DAOCS) for converting penicillin G to G-7-ADCA is developed. The major engineering strategy is to reconstitute the tricarboxylic acid (TCA) cycle of E. coli to force the metabolic flux to go through DAOCS catalyzed reaction for 2-oxoglutarate to succinate conversion. Then the glyoxylate bypass was disrupted to eliminate metabolic flux that may circumvent the reconstituted TCA cycle. Additional engineering steps were taken to reduce the degradation of penicillin G and G-7-ADCA in the bioconversion process. These steps include engineering strategies to reduce acetate accumulation in the biocatalytic process and to knock out a host β-lactamase involved in the degradation of penicillin G and G-7-ADCA. By combining these manipulations in an engineered strain, the yield of G-7-ADCA was increased from 2.50 ± 0.79 mM (0.89 ± 0.28 g/L, 0.07 ± 0.02 g/gDCW) to 29.01 ± 1.27 mM (10.31 ± 0.46 g/L, 0.77 ± 0.03 g/gDCW) with a conversion rate of 29.01 mol%, representing an 11-fold increase compared with the starting strain (2.50 mol%).